2022
DOI: 10.3390/app12178669
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Knowledge Extraction Using XAI

Abstract: Global networking, growing computer infrastructure complexity and the ongoing migration of many private and business aspects to the electronic domain commonly mandate using cutting-edge technologies based on data analysis, machine learning, and artificial intelligence to ensure high levels of network and information system security. Transparency is a major barrier to the deployment of black box intelligent systems in high-risk domains, such as the cybersecurity domain, with the problem getting worse as machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…SHAP (SHapley Additive exPlanations) [17] is a post hoc, XAI technique that has been recently used in several cybersecurity domains [47,48]. In this article, it was used to explain how input values mainly condition decisions of machine learning models, as well as to understand how the the presence of adversarial attacks may have an effect on decisions of an effective machine learning model produced for Windows PE malware detection.…”
Section: Shapmentioning
confidence: 99%
“…SHAP (SHapley Additive exPlanations) [17] is a post hoc, XAI technique that has been recently used in several cybersecurity domains [47,48]. In this article, it was used to explain how input values mainly condition decisions of machine learning models, as well as to understand how the the presence of adversarial attacks may have an effect on decisions of an effective machine learning model produced for Windows PE malware detection.…”
Section: Shapmentioning
confidence: 99%
“…The evaluation of the explanation also showed that utilizing the SHAP explanation technique to explain the generated subset of explanatory features is more robust than the other explanation techniques of LIME. Šarčević et al [1] provided both SHAP's XAI technique and If-then decision tree rules to extract information from a network attack dataset CIC-IDS2017 to mitigate network security. The challenges of these two techniques for information extraction were compared and their use in different situations was pointed out.…”
Section: B Xai For Modelsmentioning
confidence: 99%
“…C Ybersecurity refers to the aspect of protecting the individual or organization's network and information systems to defend against cyber attacks, including protecting data availability, confidentiality, and integrity [1]. In the era of rapid information technology development, network security is becoming increasingly important to networks and computer users.…”
Section: Introductionmentioning
confidence: 99%